Nucleolar TFIIE plays a role in ribosomal biogenesis and performance. Issue 19 (28th September 2021) - Phan, Tamara; Maity, Pallab; Ludwig, Christina; Streit, Lisa; Michaelis, Jens; Tsesmelis, Miltiadis; Scharffetter-Kochanek, Karin; Iben, Sebastian
Abstract: Ribosome biogenesis is a highly energy-demanding process in eukaryotes which requires the concerted action of all three RNA polymerases. In RNA polymerase II transcription, the general transcription factor TFIIH is recruited by TFIIE to the initiation site of protein-coding genes. Distinct mutations in TFIIH and TFIIE give rise to the degenerative disorder trichothiodystrophy (TTD). Here, we uncovered an unexpected role of TFIIE in ribosomal RNA synthesis by RNA polymerase I. With high resolution microscopy we detected TFIIE in the nucleolus where TFIIE binds to actively transcribed rDNA. Mutations in TFIIE affects gene-occupancy of RNA polymerase I, rRNA maturation, ribosomal assembly and performance. In consequence, the elevated translational error rate with imbalanced protein synthesis and turnover results in an increase in heat-sensitive proteins. Collectively, mutations in TFIIE—due to impaired ribosomal biogenesis and translational accuracy—lead to a loss of protein homeostasis (proteostasis) which can partly explain the clinical phenotype in TTD.